Four anti-Pelagian writings - Augustine, of Hippo, Saint, 354-430 (Fathers of the church, 1992)
"This volume brings together writings from early and late stages of Augustine's involvement in the Pelagian controversy. On Nature and Grace and on the Proceedings of Pelagius both date from A.D. 415-16 and constitute two of Augustine's most extensive treatments of the actual words of Pelagius. On the Predestination of the Saints and On the Gift of Perseverance were written in A.D. 428, near the end of Augustine's life. Augustine's opponents in his writings, he admits, are not really Pelagians at all. They were monks of Provence, led by John Cassian, who were disturbed by the more extreme consequences of the theology of grace and predestination that Augustine had worked out in his controversy with the Pelagians. Since the sixteenth century, they have been labeled "semi-Pelagians."" "Taken together, these writings provide an occasion to examine the continuity and development of Augustine's theology of grace. They also afford much insight into the fifth-century status of many theological questions that are alive today, such as the extent of the damage done to human nature by sin, the theology of original sin, the effects of baptism, and the true meaning and scope of God's salvific will." "These treatises include some of Augustine's most significant statements on grace. Intended for scholars and students of theology and philosophy, this edition includes three treatises translated for the first time since the nineteenth century, two of which are the first from modern critical texts. William Collinge's trenchant introductions offer detailed accounts of the historical and critical work done over the hundred years since the last publication."--Jacket